Kompetensi dan Relevansi Lulusan Program Studi S1 Akuntansi Reguler Sore FEB Universitas Mataram - Wirawan Suhaedi; Eni Indriani; Baiq Rosyida Dwi Astuti (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2019)
Undergraduate Program (S1) Akuntansi Reguler Sore is one of the youngest study programs at FEB Unram which has just graduated 3 (three) classes, namely the 2012, 2013, and 2014 classes. Tracer study activities are conducted to obtain information about successes and deficiencies in the education process have been taken by students, the competitiveness of graduates shown through the waiting period gets the first job, the success of graduates competes in selection, and the salary earned. The relevance (suitability) of graduate education is shown through job profile, relevance of work with educational background, benefits of courses programmed in the work, advice from graduates to improve graduate competency. In addition, the relevance of education is also shown through the opinions of graduate users about graduate user satisfaction, graduate competency and graduate advice to improve graduate competency. The results of the tracer study can be summarized as follows; graduate competency is very good, and alumni feel able to compete with graduates from other institutions, the main consideration in choosing the first job is to get experience with the waiting period to get the first job mostly between 1-3 months with one recruitment process, the most competency needed in work are the ability to cooperate in teams, computer skills, English, and understanding of accounting, while capabilities in the field of research are less needed. Stakeholders are very satisfied with the performance of alumni, especially in terms of high discipline, responsibility for work, good work performance, and good mastery of technology.